Analysis of Qur'anic Messages in the Textbooks "Qur'an" and "Heavenly Messages" for Middle School, Based on Positive Affect and Life Satisfaction Components - Shokoufe Bagheri Sharif Abadi (پژوهش در آموزش معارف و تربیت اسلامی, 2024)
The present study examines the content of Qur'anic messages in the middle school textbooks Qur'an and Heavenly Messages based on the components of positive affect and life satisfaction. The research method employed was content analysis, evaluating the use of these variables in shaping the content of the textbooks through an analysis of various units in the Qur'an and Heavenly Messages textbooks using a researcher-developed checklist. This descriptive and applied research analyzed nine textbooks (Qur'an, Heavenly Messages, and Heavenly Messages Workbook) from the 2021-2022 academic year. Findings indicate that the textbooks address happiness-related components, but with differing levels of emphasis. The component of positive affect had the highest frequency and significance, while life satisfaction had the lowest. Among happiness indices, those related to relationship with God, prayer, supplication, and smiling in interactions had the highest emphasis, whereas hope for the future and humor in interactions had the least.